2018
DOI: 10.1155/2018/7526234
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for Infantile Colic: A Systematic Review of Randomised Controlled Trials

Abstract: Introduction Infantile colic is a common condition causing considerable deterioration in the quality of life of both infants and their parents. Minimal acupuncture, a gentle needling technique without strong muscle stimulation, has primarily been used to treat this condition, but the clinical evidence of its efficacy and safety is yet to be established. The objective of this review was to assess clinical evidence of the safety and efficacy of acupuncture for infantile colic. MethodsTo identify studies for incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In complementary alternative medicine, diseases can be treated with different interventions, including acupuncture and herbal medicine, as well as manual therapy, such as tuina, massage, and chiropractic maneuvers. In fact, previous studies have reported that several manual therapy approaches and the application of acupuncture have achieved significant results in alleviating crying symptoms in children [ 4 , 48 ]. However, a systematic review on the effectiveness of tuina therapy in NC was included in only two RCTs, whereas most studies showed a limitation in terms of the risk of methodological distortion [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…In complementary alternative medicine, diseases can be treated with different interventions, including acupuncture and herbal medicine, as well as manual therapy, such as tuina, massage, and chiropractic maneuvers. In fact, previous studies have reported that several manual therapy approaches and the application of acupuncture have achieved significant results in alleviating crying symptoms in children [ 4 , 48 ]. However, a systematic review on the effectiveness of tuina therapy in NC was included in only two RCTs, whereas most studies showed a limitation in terms of the risk of methodological distortion [ 4 ].…”
Section: Discussionmentioning
confidence: 99%